Direct printing of sub-30 μm liquid metal patterns on three-dimensional surfaces for stretchable electronics. (13th February 2020) - Shin, Gyowook; Jeon, Byungjun; Park, Yong-Lae
Abstract: In this study, a liquid metal is directly printed on various types of surfaces using an automated dispensing system. A particular class of liquid metals called eutectic gallium–indium (Ga: 75.5% In: 24.5% by weight ratio) was chosen and printed on flat, inclined (20°, 30°, 40°, and 50°), and curved (   =  0.02, 0.03, 0.04, and 0.05 mm −1 ) surfaces. The inner diameter of the dispenser nozzle, the distance between the nozzle tip and the surface of the substrate, turned out to be the crucial parameters that determine the performance of printing, based on the experimental evaluation of the relationship between the trace width and the parameters. We were able to control the trace width under 200 m as small as 22 m by adjusting the parameters we tested. To the best of our knowledge, an EGaIn trace 22 m in width is the smallest one achieved by direct printing of a liquid metal on three-dimensional (3D) surfaces. Also, we were able to print not only straight lines but also curved patterns, such as spiral shapes. This will lead to the miniaturization of stretchable electronics with any pattern shapes consisting of straight lines and curves. As an example of applications of the proposed method, a micro-scale pressure sensor with a spiral trace pattern was fabricated, and its performance was evaluated with loading and unloading tests. Another application of the proposed method includes direct printing of stretchable electronics on surfaces with arbitrary shapes and curvatures. It was demonstrated with a seven-segment display circuit and soft sensors printed on a mannequin hand. We believe the proposed method and its applications will open a new space in development of soft electronics and robots.